A Study on That Attitude of Generation Y towards Social Media Advertising and the Effect on Purchasing Behaviour - Ohajionu, Uchechi Cynthia (2015)
The relevance of social media advertising in this era of cut-throat competition and tight budgeting cannot be overstressed. More than ever, marketing managers are required or expected to justify their advertising budget – in terms of how it will impact sales and revenue. This implies that the era of ‘trial and error’ in advertising to maximize return on investment (spending) on advertising in form of sales, revenue, and profits. Findings from this study will help advertising managers to ensure more efficient utilization of their budget and development of more effective advertising strategy, especially when formulating strategies for Generation Y in Malaysia. It also adds to the existing body of knowledge in the era of social media advertising which is still limited. This research investigates the attitude of Generation Y towards social media advertising and what motivate consumers to purchase or not to purchase on sites advertised on social media. Moreover, it examines how businesses can effectively target and engage consumers by determining their attitude and purchase intention and integrating these into their advertising plans and promotion mix. The study through data collected from 1,087 Generation Y consumers in Malaysia examines the effect of belief factors (lifestyle, privacy and security concern, entertainment and credibility) on attitude towards social media advertising. The data was analysed in three ways: descriptive statistic were provided to determine the mean and standard deviation scores for the four belief factors; analysis of variance (ANOVA) tests were conducted to determine the relationship between the demographic profiles and respondents’ purchase intention; and Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed to assess the hypothetical relationships between the belief factors and attitude towards social media advertising, purchase intention and actual purchase. Results of the analysis revealed that the belief factors (lifestyle, privacy and security concern, entertainment and credibility) showed a positive influence on attitude towards social media advertising. Implications of these findings for researchers and advertisers were further discussed.